PENDAMPINGAN BELAJAR MATEMATIKA SEKOLAH DASAR BERBASIS PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK DI KELURAHAN TODABELU - Maria Editha Bela; Wilibaldus Bhoke; Florintina Elvin Bara; Natalia Rosalina Rawa; Maria Carmelita Tali Wangge; Melkior Wewe; Bernadus Agustinus Dhaga Wewu Bili; Beatriks Sare; Kristiyanti Kurnia Dhajo (STKIP Citra Bakti, 2022)
Tutoring activities for students at various levels of education is one of the mandatory programs in the 2021 STKIP Citra Bakti Real Work Program. This activity was carried out at SDN Koeloda Inpres, located in Todabelu, Golewa. Through Real Work Program, students are expected to gain experience in social life and apply their academic knowledge. One of the community service programs organized by the STKIP Citra Bakti College through Real Work Program in 2021 academic year is the tutoring program. Students of Mathematics Education Study Program carried out tutoring programs in elementary schools based on the Realistic Mathematics Education approach during the pandemic, in order to increase students' motivation and interest in learning. The general assumption so far that tutoring is considered to reduce students' playing time was proven otherwise. Tutoring activities actually provided value for children's learning processes, especially during the COVID-19 pandemic where students did not get maximum education materials from teachers, because they have to study online. Realistic mathematics education is an approach that places students' reality and experience as the starting point of learning where students are given the opportunity to construct their own mathematical knowledge through real problems that exist. That is, this learning places the subject matter in a meaningful context. To improve students' understanding, learning mentoring activities were based on the Realistic Mathematics Education approach. Realistic Mathematics Education (RME) was used to increase students' interest in learning and refers to students being able to understand and improve students' independent learning alternatives.